Analysis of the Mechanism of Restitution and Its Impact on the Financial Recovery of the State Due to Corruption Offenses - Foster, Armen (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This research aims to examine the effectiveness of the restitution mechanism, as regulated in Article 18 of Law Number 31 of 1999 on the Eradication of Corruption, as amended by Republic of Indonesia Law Number 20 of 2001 on Amendments to Law Number 31 of 1999 on the Eradication of Corruption, in reducing state financial losses due to corruption offenses. This study examines the implementation of the restitution process and its impact on state financial recovery using a qualitative normative juridical method. The researcher demonstrates that imposing restitution as an additional sanction is crucial in recovering state financial losses caused by corruption. However, challenges arise in the form of substitutionary penalties that reduce the effectiveness of restitution, as well as the tendency of offenders to choose imprisonment over fulfilling their obligation to make restitution. The lack of coordination among relevant parties also affects the implementation of restitution. To enhance the effectiveness of restitution, a comprehensive approach is needed, strengthening legal compliance and coordination among law enforcement agencies, judicial institutions, and auditing institutions. By addressing these challenges, the restitution mechanism can significantly contribute to reducing state financial losses caused by corruption